Fatwa, Qanun, Qadha, and Ijtihad: Understanding Their Differences and Functions - Wiseno, Sekar Galuh Putri; Apriantoro, Muhamad Subhi (Ethica: International Journal of Humanities and Social Science Studies, 2024)
This research aims to discuss the concepts of Fatwa, Qanun, Qadha, and Ijtihad. These concepts require robust definitions to address the issues at hand. The biggest challenge lies in the differences in interpretation and the potential conflicts with Sharia principles, which must be approached with caution. In other words, the application of fatwa, qanun, qadha, and ijtihad in interpreting contemporary Islamic law has a significant impact on the sustainability and adaptability of the law amidst changing times. Therefore, their implementation must be carried out wisely to avoid violating the fundamental principles of Islamic law. This research employs a qualitative, literature-based research method to explore various journals, books, and historical developments of fatwa, qanun, qadha, and ijtihad within Islamic law, as well as their urgency and limitations in addressing the challenges of changing times and social contexts. The results are expected to provide a deeper understanding of their role in Islamic law while detailing their limitations to offer a comprehensive view of these concepts in an ever-evolving context. Additionally, this research is anticipated to contribute to academic discourse on Islamic law and serve as a foundation for further research in this field.